In vitro evaluation of microencapsulated organic acids and pure botanicals as a supplement in lactating dairy cows diet on in vitro ruminal fermentation - Lobo, Richard Roberto (2023)
The utilization of microencapsulated organic acids and pure botanicals (mOAPB) is widely used in the monogastric livestock industry as an alternative to antibiotics; in addition, it can have gut immunomodulatory functions. More recently, an interest in applying those compounds in the ruminant industry has increased; thus, we evaluated the effects of mOAPB on ruminal fermentation kinetics and metabolite production in an in vitro dual-flow continuous-culture system. For this study, two ruminal cannulated lactating dairy Holstein cows were used as ruminal content donors, and the inoculum was incubated in eight fermenters arranged in a 4 × 4 Latin square design. The basal diet was formulated to meet the nutritional requirements of a 680-kg Holstein dairy cow producing 45 kg/d of milk and supplemented with increasing levels of mOAPB (0; 0.12; 0.24; or 0.36% of dry matter [DM]), which contained 55.6% hydrogenated and refined palm oil, 25% citric acid, 16.7% sorbic acid, 1.7% thymol, and 1% vanillin. Diet had 16.1 CP, 30.9 neutral detergent fiber (NDF), and 32.0 starch, % of DM basis, and fermenters were fed 106 g/d split into two feedings. After a 7 d adaptation, samples were collected for 3 d in each period. Samples of the ruminal content from the fermenters were collected at 0, 1, 2, 4, 6, and 8 h postmorning feeding for evaluation of the ruminal fermentation kinetics. For the evaluation of the daily production of total metabolites and for the evaluation of nutrient degradability, samples from the effluent containers were collected daily at days 8 to 10. The statistical analysis was conducted using MIXED procedure of SAS and treatment, time, and its interactions were considered as fixed effects and day, Latin square, and fermenter as random effects. To depict the treatment effects, orthogonal contrasts were used (linear and quadratic). The supplementation of mOAPB had no major effects on the ruminal fermentation, metabolite production, and degradability of nutrients. The lack of statistical differences between control and supplemented fermenters indicates effective ruminal protection and minor ruminal effects of the active compounds. This could be attributed to the range of daily variation of pH, which ranged from 5.98 to 6.45. The pH can play a major role in the solubilization of lipid coat. It can be concluded that mOAPB did not affect the ruminal fermentation, metabolite production, and degradability of dietary nutrients using an in vitro rumen simulator.